Effect of equal channel angular pressing process on drawability of DC04 steel sheets - Talantikite, Massil; Mebarek, Abdelmalek; Zaaf, mohamed; BOUKEFFA, Saida (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
Equal channel angular pressing (ECAP) is a severe plastic deformation processing (SPD) technique that induces significant changes in the crystalline structure of the material, resulting in improved mechanical properties. The objective of this experimental work is to study the influence of this process on the drawability of DC04 steel sheets. A pack of six sheets placed in sandwich were deformed at room temperature with an inside channel angle of 120° for 1 passe. A characterization by hardness measurement and tensile test was conducted. In addition, optical microscope observation and X-ray diffraction (XRD) analysis were performed. A finite element simulation using Abaqus was implemented to allow a thorough analysis of the process. Finally, the Erichsen test was used to assess the drawability of the sheet that present the best mechanical propriety, A finite element simulation also was used with Abaqus to allow a better analysis of the process. The results showed an increase in microhardness, reaching up to 64%. The microstructure study showed a grain refinement of about 70% with the appearance of a slight texture and without phase change. The tensile test showed an increase in yield stress (Re) and the ultimate tensile strength (Rm), and a diminution of elongation (A%) and the Strain Hardening Exponent (n) were observed. The Erichsen test showed a slight decrease, of the order of 10% of the Erichsen cupping index (IE), therefore, it should be noted that the sheets have retained a good suitability for deep drawing.